Anxiety and Depression Symptom Level and Psychotherapy Use Among Music and Art Students Compared to the General Student Population - Vaag, Jonas; Bjerkeset, Ottar; Sivertsen, Børge (Frontiers in Psychology, 2021)
PURPOSE: Previous epidemiological studies have shown higher levels of anxiety and depressive symptoms among professional musicians, compared to the general workforce. Similar findings have been observed for psychotherapy use among musicians. To date, large-scale investigations of prevalence rates among music and arts students are lacking. METHODS: 880 students from music and arts institutions and faculties were derived from a national health student survey for higher education in Norway (the SHoT study). They were compared to a sample of the general student population (n=48,729). We used logistic regression analysis, adjusting for age, sex and semesters of study. RESULTS: Music and arts students reported higher rates of anxiety (OR 1.60 (1.38-1.85), Prevalence difference (PD) 9.6 (6.3-12.8)) and depression symptoms (OR 1.41 (1.22-1.62), PD 7.9 (4.5-11.2)) compared to the general student force. Similar patterns were observed for self-reported mental disorders (OR 1.71 (1.46-2.01), PD 8.1 (5.3-11.0)), as well as psychotherapy use (OR 1.91 (1.60-2.29), PD 7.4 (4.9-9.9)) in music and arts students. CONCLUSIONS: Our findings are consistent with studies comparing musicians to the general workforce, and indicate that challenges also exist at student level, and not only after becoming a professional in the performing arts, which is important when planning health-related measures. These findings have the potential to inform on health promotion and services in the educational system.